Analisis kinerja keuangan pada PT. XT - Tumiwa, Samuel; Mawikere, Lidia M. (Riset Akuntansi dan Portofolio Investasi, 2024)
The company's strong financial performance is an attractive feature for investors. This research analyzes the financial performance of the company using ratio analysis and common size analysis. The financial ratios are used to evaluate the company's financial performance, while the common size approach is used to identify the reasons for changes in the profit and loss statement and financial position statement. The language used is clear, objective, and value-neutral, with a formal register and precise word choice. The text adheres to conventional structure and formatting features, with consistent citation and footnote style. The structure is logical and well-organized, with causal connections between statements. The text is free from grammatical errors, spelling mistakes, and punctuation errors. No changes in content have been made. Descriptive qualitative research that uses both quantitative and qualitative data. The research findings indicate good financial performance in terms of liquidity ratios and Gross Profit Margin (GPM), but not for Net Profit Margin (NPM). The solvency ratio is very good. The analysis utilizing the common size approach indicates an increase in the percentage of cash and cash equivalents, inventory, operational expenses, additional capital, and current debt, as well as a decrease in receivables and net profit from 2020-2022.